Effectiveness of comprehensive neurorehabilitation treatment on the cognitive function of patients with relapsing-remitting multiple sclerosis - Làzaro Aurelio Vàzquez Gòmez; Carlos Hidalgo Mesa; Yunier Broche Pèrez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: Therapeutic alternatives should not focus their efforts on the rehabilitation of specific cognitive domains, but value the use of multimodal intervention strategies, with the purpose of minimizing the negative factors that intervene in the cognitive health of patients with multiple sclerosis. Objective: to determine the effectiveness of comprehensive neurorehabilitation treatment on the cognitive function of patients with relapsing-remitting multiple sclerosis. Methods: a quasi-experimental study was carried out with two groups (a study group and a control group) in patients diagnosed with relapsing-remitting multiple sclerosis. Each group was made up of 39 patients. Statistical methods required the use of a repeated test study, variant of ANOVA. For the two-moment tests, the one-way ANOVA concept was used. Results: after the intervention, in the study group, an increase in the scores in the tests of processing speed, working memory-cognitive flexibility, verbal fluency and inhibitory control was obtained; as well as decreased levels of fatigue. A significant improvement in the emotional state of the study group was verified, showing a decrease in the state of anxiety and depression. Conclusions: the comprehensive neurorehabilitation process was effective in reducing depression and anxiety levels in patients, in addition to improving cognitive functioning in the group of patients who completed the process, which shows the viability of a comprehensive neurorehabilitation approach and its effectiveness utility to improve quality of life in adults with multiple sclerosis.